Clinical trial assessing the safety of edoxaban with concomitant chemotherapy in patients with gynecological cancer-associated thrombosis (EGCAT study) - Tadashi Oride; Kenjiro Sawada; Aasa Shimizu; Yasuto Kinose; Tsuyoshi Takiuchi; Michiko Kodama; Kae Hashimoto; Eiji Kobayashi; Eiji Nakatani; Tadashi Kimura (Thrombosis Journal, 2023)
Abstract Background Gynecological cancer is one of the highest risk factors for cancer-associated thrombosis (CAT). Although low-molecular-weight heparin (LMWH) is recommended as an anticoagulant for treating CAT, recent studies have shown that direct oral anticoagulants (DOACs) are an acceptable alternative. Patients with cancer require a series of chemotherapies concomitantly with DOAC administration; however, the extent to which these drugs influence DOAC blood concentrations is unknown. In this study, we measured the plasma concentration of edoxaban during chemotherapy for gynecological cancers to determine its safety. Methods Patients histologically diagnosed with ovarian or uterine corpus cancer and CAT were recruited after primary surgery and before the initiation of postoperative adjuvant chemotherapy, including paclitaxel. Patients were administered edoxaban (30 or 60 mg) orally for CAT. The plasma concentrations of edoxaban and active factor Xa were determined and their percentage change before and after chemotherapy was calculated. Additionally, blood coagulation tests were analyzed. Results Sixteen patients with gynecological cancer (12 with ovarian cancer and 4 with uterine corpus cancer) were enrolled. Among these, 15 samples were collected one day after chemotherapy initiation. During chemotherapy, the trough concentration of edoxaban changed from 17.6 ± 10.6 to 20.0 ± 15.6 ng/ml, and the mean percentage change in edoxaban concentration was 14.5%. Therefore, the trough concentrations of edoxaban, which represent excretion capacity, were not significantly increased by chemotherapy with paclitaxel. The area under the plasma edoxaban concentration–time curve and the active factor Xa concentration were also unaffected. Conclusion Patients with CAT and ovarian or uterine corpus cancer administered edoxaban orally showed no significant increase in the trough concentration of edoxaban while undergoing chemotherapy. This suggests the safety of edoxaban use during the treatment of gynecological cancers. Trial registration EGCAT study; Japan Registry of Clinical Trials, jRCTs051190024.